Innovative work practices, information technologies and working conditions: evidence for France - Philippe Askenazy; Eve Caroli (Institute for the Study of Labor (IZA), 2006)
We investigate the impact of new work practices and information and communication technologies (ICT) on working conditions in France. We use a unique French dataset providing information on individual workers for the year 1998. New work practices include the use of quality norms, job rotation, collective discussions on work organization and working time flexibility. Working conditions are captured by occupational injuries as well as indicators of mental strain. We find that workers involved in the new practices face working conditions that are significantly worse than those of workers in non innovative work practices. But, the picture is mixed for ICT that seem to make the workplace safer and less risky
Keywords: 330